Initial sites, expansion and convergence of Quechua, Aymara and Puquina - Calsín Vilca, David Peter (2020)
The historical past of the major languages ??of ancient Peru, mainly the Andean languages, is still in constant discussion, despite having an academic roots that dates back more emphatically to the middle of the last century. The academic meetings of Cambritge (2008), Lima (2009) and Leipzing (2011) express their concern in reviewing the interpretive framework of the social and evolutionary development of the Andean linguistic reality; which is why, we offer some work on it.